Placenta Percreta in Second Trimester Pregnancy Causing Early Spontaneous Uterine Rupture: A Case Report and Literature Review - Santoso, Dhanny Primantara Johari; Nugrahani, Annisa Dewi; Rachmawati, Anita; Pribadi, Adhi; Anwar, Anita Deborah; Effendi, Jusuf Sulaeman (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Uterine rupture following to placenta accreta spectrum disorder such as placenta percreta in second trimester pregnancy is a very rare obstetrical condition. This condition occurs primarily in the third trimester and leads to both fetal and maternal life-threatening complications. CASE PRESENTATION: We report a 28-year-old woman in 24−25 weeks of gestation with scars from previous cesarean delivery came to emergency department due to acute abdomen following to intraperitoneal hemorrhage. From diagnostic modalities, it was found uterine rupture from the varicose veins of placenta percreta without tears in the uterus. Total hysterectomy was performed with good recovery and histopathology result showed placenta percreta. CONCLUSION: In spite of being a rare case in second trimester of pregnancy, spontaneous rupture of uterus due to placenta percreta should be considered in the case of a patient with placenta percreta who presents with severe abdominal pain and acute intraperitoneal hemorrhage, even in the second trimester of gestation.